Determination of the MESEP Events of 2-9th April 2001 According to ERNE/SOHO Observation - Fadhel, Aseel; Al-Sawad, Amjad; Abood, Kamal (Iraqi Journal of Science, 2025)
On 2-9th April 2001 the Energetic and Relativistic Nuclei and Electron (ERNE) instrument on the Solar and Heliospheric Observatory (SOHO) observed three gradual solar energetic particle (SEP) events separated by 9 hour and 7days respectively, in association with three effective solar flares and coronal mass ejections (CMEs).In this paper, a study of MESEP events was considered. As the definition of this phenomenon suggested there might be many sources for each MESEP event. This event has been examined in order to view the different sources that might relate to suspected accelerator of the SEPs. A careful analysis for the spectra and associated emission with such eruptions was made. Soft X-ray emission was observed by the Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES)Geostationary Operational Environment Satellite (GOES) Geostationary Operational Environment Satellite (GOES) was used to indicate the associated solar flares, earth radio stations were used to determine the associated radio emissions. While three instruments, beside (ERNE) were used from the SOHO satellite, the Large Angle Spectrometric Coronagraph (LASCO) to follow the CMEs, the Extreme-ultraviolet Imaging Telescope (EIT) for observing the Morton waves to indicate the CME location and the Charge, Element, and Isotope Analysis System CELIAS to indicate the shock waves caused by CMEs.